Comment on: Phase I/II study of adding intraperitoneal paclitaxel in patients with pancreatic cancer and peritoneal metastasis. Issue 5 (12th March 2021) - Rau, Kun-Ming; Chang, Chao-Sung; Pei, Sung-Nan; Hsieh, Meng-Che; Tsai, Yu-Fen; Chiu, Chong-Chi
Abstract : Our submission is the Correspondence to the text with the title of "Phase I/II study of adding intraperitoneal paclitaxel in patients with pancreatic cancer and peritoneal metastasis". It was published in Br J Surg 2020; 107: 1811–1817.